The Effect of Mangaplus Application Toward Student’s Reading Comprehension of Narrative Text at Tenth Grade of Senior High School 8 Muaro Jambi - Pasada, Adrieco; Silfia, Efa; Dinata, Ridho Praja (JELT: Journal of English Language Teaching, 2024)
This research aims to find out the effect of using the MangaPlus application on students' reading comprehension in the narrative text at tenth-grade students of SMAN 8 Muaro Jambi. This research used a quantitative research design with a quasi-experimental approach, including quantitatively accepted pre- test and post-tests. This research uses tenth-grade students of SMAN 8 Muaro Jambi from XE1 Fase and XE3 Fase as a sample class. Before offering treatment, the exam should assess the student's reading comprehension with 25 multiple-choice reading tests. In the pre-test experimental group, the researcher received 32 sample scores with mean values of 54, 70, 88, and. 32. After treatment, the researcher acquired 32 sample scores with means of 55, 58, 80, and 32. Based on the result of the research it can be concluded that the Mangaplus application can help students to enhance their reading skills.Keywords: Reading Comprehension, Narrative Text, Mangaplus Application